1993
DOI: 10.1002/1097-0142(19930215)71:4<1258::aid-cncr2820710415>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer risk associated with proliferative breast disease and atypical hyperplasia

Abstract: Background. Women with proliferative breast disease (PD) have been observed to have an increased risk of breast cancer. The authors evaluated the effect of PD on breast cancer risk in a case–control study among participants of the Breast Cancer Detection Demonstration Project (BCDDP). Methods. More than 280,000 women were screened in the BCDDP at 29 centers. Study subjects were selected from BCDDP participants who underwent biopsy that revealed benign breast tissue. There were five BCDDP centers for which hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
247
2
14

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 484 publications
(275 citation statements)
references
References 14 publications
10
247
2
14
Order By: Relevance
“…Consistent with other studies (28,30), we found that women with fibroadenoma who have undergone surgical treatment are two times less likely to develop breast cancer as compared to those who did not undergo surgery for the same disease. The increased risk of breast cancer among those surgically treated for 'other BBD' in this study may imply that women with higher risk categories of BBD are highly susceptible to breast cancer as has been reported previously (11,20,35). Future studies may need to address whether early detection and intervention for any type of BBD reduces the risk breast cancer and should be recommended.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Consistent with other studies (28,30), we found that women with fibroadenoma who have undergone surgical treatment are two times less likely to develop breast cancer as compared to those who did not undergo surgery for the same disease. The increased risk of breast cancer among those surgically treated for 'other BBD' in this study may imply that women with higher risk categories of BBD are highly susceptible to breast cancer as has been reported previously (11,20,35). Future studies may need to address whether early detection and intervention for any type of BBD reduces the risk breast cancer and should be recommended.…”
Section: Discussionsupporting
confidence: 68%
“…Based on these types of pathologic diagnoses for BBD, the Cancer Committee of the College of American Pathologists recommended 4 risk categories of BBD in 1985, Appendix I (9,10). The association of the high risk categories (3 and 4) of BBD (eg, atypical hyperplasia and carcinoma in situ) with invasive breast cancer risk is well established (8,11,12). However, the ANDI (Aberrations of Normal Development and Involution) classification of BBD and recent studies have suggested that the risk of breast cancer may also be associated with the two lower risk categories (1 and 2) of BBD that include fibroadenoma, cysts, mastitis, fibrosis, adenosis and hyperplasia without atypia (10,13,14).…”
mentioning
confidence: 99%
“…Women with moderate to florid hyperplasia, papilloma with fibrovascular core, or well-developed sclerosing adenosis in a biopsy specimen have a slightly increased risk of developing breast cancer relative to comparable women who have had no breast biopsy. The demonstration of either ductal or lobular atypical hyperplasia is consistent with a fourfold to fivefold increased risk of developing invasive cancer (2,3). Family history of breast carcinoma doubles this risk (8 -10 times).…”
mentioning
confidence: 75%
“…3,4 The earliest lesion associated with breast cancer is epithelial hyperplasia lacking atypia (EHLA), which has a 1.5-to 2-fold increased risk of development of breast cancer. [5][6][7][8] A slight increase in ER-positive cells has been described in these earliest lesions. 3 In our study, we investigated the relationship between ER␣ expression in EHLA and subsequent risk of invasive breast cancer.…”
mentioning
confidence: 95%